Do palco ao écran: eles não usam black-tie - Schmidt, Laila Rotter (Universidade Federal de São Carlos, 2012)
This research aims to comprehend the creative process of the movie "Eles não usam black-tie" (They don't wear black-tie) (1981), directed by Leon Hirszman, based on the homonymic play written by Gianfrancesco Guarnieri, using theoretical references provided by the line research "Procedural Critics" (as proposed by Cecilia Salles) and the documents related to the creation of the film, such as Arguments, scripts, Storyboard, among others. Considering the passage from the play text to the film as a process of "intersemiotic translation" (following Roman Jakobson), or "transcreation" (as established by Haroldo de Campos), we propose an approximation to Hirszman's creative thought, artist witch, as Guarnieri, has marked the Brazilian political and cultural scenario for the past decades.
Keywords: Cinema brasileiro; Hirszman, Leon, 1937-1987; Transcriação audiovisual; Processos criativos; Brazilian cinema; Transcreation; Creative procedural critics; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA